(untitled) (Revista de Estudos da Linguagem, 2024)
this article aims to analyze argumentative strategies used in the dissemination of hate speech against ethnic, gender/sexual orientation and religious minorities on Facebook. Manual collection of potentially offensives comments was carried out in a way that the corpus is composed by 225 comments with lgbtphobic aspect, 194 comments with racista content and 181 comments which presents possible religious intolerance, adding up 600 comments. The data was analyzed throuth works that considers argumentation as a discoursive practice (AMOSSY, 2018; CHARAUDEAU, 2008, 2010), as well as works about hate speech (FORTUNA; NUNES, 2018). In the end, we present some argumentative categories of hate speech, which can be applied to judicial expertise, in the escope of Forensic Linguistics, and to corpus annotation tasks in the ambit of Computational Linguistics.